ANALISIS PROSES PENDISTRIBUSIAN BARANG DAN LOYALITAS JASA TRANSPORTASI DI PT. ASIA PASIFIC FIBERS Tbk KALIWUNGU - Ady Prasetya (Jurnal Ekonomika dan Bisnis, 2019)
Ady Prasetya. Analysis of Goods Distribution Process and Loyalty of Transportation Services at PT. Asia Pacific Fibers, Tbk Kaliwungu. Faculty ofEconomics and Business. Selamat Sri University (UNISS) Management Study Program Kendal. 2018.This study aims to determine the process of distribution of goods and loyalty of transportation services at PT. Asia Pacific Fibers, Tbk Kaliwungu. The research method used is a qualitative method. This type of research is qualitative descriptive research.The population and sample in this study are the leaders and employees of PT. Asia Pacific Fibers, Tbk Kaliwungu. Data analysis in this study uses qualitative data analysis through interviews and observations directly at the company.The results of this study indicate that the distribution process of goods has a relationship with the loyalty of transportation services at PT. Asia Pacific Fibers, Tbk Kaliwungu. This is indicated by the guaranteed delivery of yarn PT. Asia Pacific Fibers, Tbk Kaliwungu.